Particle detrapping under AC electric field effect as the resonance process - Antufyev, A.Yu.; Shishkin, A.A. (Вопросы атомной науки и техники, 2000)
Detrapping / retrapping processes of the particle under the AC parallel electric field is studied by the analytical methods and the numerical integration of guiding center equations. It is shown that these processes can be considered as the resonance between the bounce frequency of the trapped particle and the frequency of AC parallel electric field.